PORTARIA Nº 18, DE 19 DE JANEIRO DE 2015 - Rodolfo Alves Silva (DOU, nº 15, Seção 2 de 22/01/2015, p. 40, 2015)
Designa novo servidor para exercer a função de Coordenador da PRM-Monteiro/PB, Nível I, FC-3.